MBCL-34. EFFICACY OF METHOTREXATE (MTX) ACCORDING TO MOLECULAR SUB-TYPE IN YOUNG CHILDREN WITH MEDULLOBLASTOMA (MB): A REPORT FROM CHILDREN'S ONCOLOGY GROUP PHASE III TRIAL ACNS0334. (4th December 2020) - Mazewski, Claire; Kang, Guolian; Kellie, Stewart; Gossett, Jeffrey; Leary, Sarah; Li, Bryan; Aridgides, Paul; Hayes, Laura; Reddy, Alyssa; Shaw, Dennis; Burger, Peter; Judkins, Alexander; et al.
Abstract: ACNS0334, a Phase 3 trial, compared outcomes of children <36 months treated with intensive chemotherapy +/-high-dose methotrexate. Nodular-desmoplastic M0-stage MB were excluded. Treatment included 3 induction cycles (cyclophosphamide/etoposide/vincristine/cisplatin+/-mtx) and 3 consolidation cycles (carboplatin/thiotepa with stem cell rescue). Radiation (RT) was at physician discretion. Molecular sub-typing was by DNA-methylation. Log-rank testing was used to compare survival differences. Molecular sub-typing of 38 MB identified 11 Sonic Hedgehog (SHH), 25 Group 3 (GP3), 2 Group 4 (GP4). Five-year survival (OS) was 100% for 5 SHH with MTX and 4 SHH without MTX; 80% for 10 GP3 with MTX, 40% for 15 GP3 without MTX (p=0.025). Only 6/14 survivors received RT: 4 for residual following therapy (1 SHH and 3 GP3) and 2 GP3 salvaged after progression. Two GP3 deaths were associated with toxicity; all others were due to disease. Histology among SHH was nodular-desmoplastic (8) or classic (3); GP3 histology was classic (17) or anaplastic (7). Whole-exome sequencing identified 6 somatic PTCH1 and 1 germline SUFU alteration(s) among 9 SHH. Among GP3, no p53 mutations were found; copy-number analysis identified 5/25 with myc-amplification, 5/25 iso17q, 11/25 with 8 loss, 14/25 with loss of 11. Among GP3, 14/19 had no significant germline mutation. ACNS0334 achieved 100% survival for metastatic SHH. Benefit of methotrexate was observed in GP3 MB supporting incorporation of methotrexate into standard therapy for GP3. Upfront central pathology review and molecular sub-typing are critical for future clinical trial risk stratification of young children with embryonal tumors.